Presenting a Model of Resilience Based on Individual Factors: The Mediating Role of Emotion-Focused Coping Strategy - Abdullahi, Masoumeh; Soltani, Amanullah; Manzari Tavakoli, Alireza; Kamyabi, Mitra (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study aimed to present a model of resilience based on individual factors and the mediating role of emotion-focused coping strategies. Methods and Materials: This research is descriptive-correlational, and the statistical population included all male and female undergraduate, master's, and doctoral students enrolled at the Islamic Azad University, Yazd Branch, in the academic year 2023-2024, totaling 9,550 individuals. The statistical sample size was determined using a single-stage cluster sampling method based on Morgan's table, accounting for a 10% dropout rate, resulting in the selection of 420 participants. The instruments used for data collection were the Connor-Davidson Resilience Scale (Connor & Davidson, 2003), the Spiritual Well-Being Questionnaire (Paloutzian & Ellison, 1983), the God Attachment Questionnaire (Ghobari Bonab & Hadadi Kouhsar, 2011), the Davis Empathy Questionnaire (Davis, 1983), the Self-Compassion Scale (Raes, 2011), Lazarus and Folkman’s Coping Strategies Questionnaire (1980), the Cognitive Emotion Regulation Questionnaire (Garnefski et al., 2001), and the Rosenberg Self-Esteem Scale (Rosenberg, 1965). Data analysis was conducted using structural equation modeling (SEM) with SPSS 22 and Smart PLS 4 software. Out of the distributed questionnaires, 398 were deemed analyzable. Findings: The data analysis results revealed that self-esteem, spiritual well-being, God attachment, emotional regulation, and empathy had direct effects on resilience, and indirect effects on resilience were mediated by emotion-focused coping strategies. However, self-compassion had a direct effect on resilience but did not show an indirect effect mediated by emotion-focused coping strategies. Overall, given that the Q² values for coping strategies and resilience were 0.162 and 0.380, respectively, it can be concluded that the model possesses predictive power for coping strategies concerning research variables and resilience. Conclusion: The final model, encompassing exogenous variables (self-esteem, self-compassion, spiritual well-being, God attachment, emotional regulation, and empathy), the mediating variable (emotion-focused coping strategies), and the endogenous variable (resilience), was tested using several fit indices, demonstrating the appropriateness and adequacy of the final model.